If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -14 = 28 + x Reorder the terms: -14 + X = 28 + x Solving -14 + X = 28 + x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + X = 28 + 14 + x Combine like terms: -14 + 14 = 0 0 + X = 28 + 14 + x X = 28 + 14 + x Combine like terms: 28 + 14 = 42 X = 42 + x Simplifying X = 42 + x
| X(x+1)=0.75 | | 89-5x=31x+21 | | 5x+2(x-3)=-15 | | 6(x-6)+6=8x+6 | | 46-4x=6x-4 | | 8+9p+4(11-2p)= | | 40x+10(1.5x)=1500 | | -10n-3+2(5+6n)= | | .33(x-21)=.66 | | x+2+3x-4+2x+6= | | -2=b-150 | | 7+n=-8 | | 9.5-0.315x^2+0.743x=0 | | 2x-13=-81 | | 7-0.33333n=-28 | | 7-0.33333=-28 | | 46.5=3(4+5x) | | 2n+25=45 | | 48=5x+18 | | 2x-3+5(5x+2)= | | 10-3n=12 | | V-5/8=-1/4 | | 3n-10=12 | | f(x)=x^6/(2lnx) | | 32a^3-24a^2+36a=0 | | 1/x=-27/28 | | 80+13x=145 | | z/5-6=10/3 | | -7(v+2)=-4v-44 | | 3.53x+100=12.4609+10x | | -8h-8(2-4h)= | | 6(2n+3)=6(4n+5)+5 |